2019
DOI: 10.3390/computers8040077
|View full text |Cite
|
Sign up to set email alerts
|

Review on Techniques for Plant Leaf Classification and Recognition

Abstract: Plant systematics can be classified and recognized based on their reproductive system (flowers) and leaf morphology. Neural networks is one of the most popular machine learning algorithms for plant leaf classification. The commonly used neutral networks are artificial neural network (ANN), probabilistic neural network (PNN), convolutional neural network (CNN), k-nearest neighbor (KNN) and support vector machine (SVM), even some studies used combined techniques for accuracy improvement. The utilization of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 51 publications
0
33
0
3
Order By: Relevance
“…It was also stated that the image analysis combined with genetic analysis is a useful method for explaining the main processes that influence salinity tolerance in plants. In this context, − recent studies have been looking for simple, accurate and non-destructive methods to evaluate how abiotic stressors affect plants’ growth [ 7 , 19 , 30 , 32 ]. Regarding plant architecture, fractal dimension has been proven to be a good indicator for analysing plant foliage changes due to salinity.…”
Section: Introductionmentioning
confidence: 99%
“…It was also stated that the image analysis combined with genetic analysis is a useful method for explaining the main processes that influence salinity tolerance in plants. In this context, − recent studies have been looking for simple, accurate and non-destructive methods to evaluate how abiotic stressors affect plants’ growth [ 7 , 19 , 30 , 32 ]. Regarding plant architecture, fractal dimension has been proven to be a good indicator for analysing plant foliage changes due to salinity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that image processing and computer vision techniques can help to identify plant diseases ( Golhani et al, 2018 ). The accuracy of the classification along with the image pre-processing could yield 90.5% recognition rate ( Azlah et al, 2019 ). Thus far, only a few studies have been carried out to predict the charcoal rot disease development onset ( Nagasubramanian et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…CNN is better than other classifiers as it identifies and extracts the image features at the same time. Because of this reason, it is faster than other neural networks [6].…”
Section: Convolutional Neural Networkmentioning
confidence: 99%